Improving the performance of human hip implants by improving the processing quality and geometric accuracy of their spherical surfaces - Raul Turmanidze; G. Popkhadze; К. Inasharidze (Mechanics and Advanced Technologies, 2020)
In view of the fact that the endo-prosthesis heads of human hip-joint are operated in extreme conditions, in respect of load, the selection of corresponding material and also increase of precision and quality of machining of spherical surfaces is rather topical task.